PENGARUH TIPE TUTUPAN LAHAN TERHADAP IKLIM MIKRO DI KOTA BITUNG - Yorri Y. J. Sanger; Rino ., Rogi; Johan A. Rombang (AGRI-SOSIOEKONOMI, 2016)
This study aimed to analyze the effect of land cover types to micro-climate of and analyze the effect microclimate to the trees and open land towards amenities environment for human. The City of Bitung has selected as a research site because it planned for mega projects. They are Special Economic Zones (KEK), International Relations Ports and Manado-Bitung Highways. The research used primary and secondary data. The parameters measured for each land cover includes the elements of microclimate namely: Air Temperature, Humidity and Solar Radiation. Data analysis using techniques T test, F test and Analysis of amenities based on the data of air temperature and humidity, it can be calculated by Temperature Humadity Index (THI). The measurement results microclimate taken at four different land cover that is at the city park, Central Business District (CBD), housing and industry. The results of this study prove the hypothesis that there are differences in the average value of the temperature and humidity in the trees, open land. Tree vegetation structures more effectively reduce the air temperature. The structure of the vegetation canopy of trees that have rounded and more densely branched patterns, height being between 6-10 m and serves to overshadow proved more effective in improving amenities in the surrounding area. Based on the value of THI, all land cover both parks, CBD, residential and industrial categorized uncomfortable because the average is at a value> 27. Housing area has very little green space. One of the efforts to improve the quality of the microclimate in order to enhance the user experience is to provide a good environment garden by planting vegetation predominant tree combined with shrubs and grasses to balance and harmonize between buildings and the environment also have aesthetic value. In the industrial area, the high levels of air pollution resulting from the production process so that recommended a good landscape arrangement, by expanding area of town forest and planting vegetation of trees that can absorb large numbers of pollutants result in healthy and fresh air for the region.